THE STUDY OF THE EFFECT OF ETHICAL CLIMATE ON THE UNIVERSITY STUDENTS' EDUCATIONAL ATTITUDES IN OPERATING ROOM - MIANDOAB, NAZANINYOUSEFIAN; Zare, Sadegh; MahnazShahrakipour, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Health-care students should be properly trained to be able to solve the society problems in the future. One of the factors affecting the academic progress of students is student's educational attitudes that are affected by the factors such as their learning environment's climate. The aim of the current study is studying the ethical climate on the university students' educational attitudes in the operating room of the medical science university in Zahedan. Methods: In this descriptive-analytical study, the students were selected by census method (62 students). To collect the data, a three-part questionnaire was used that the first part was related to the demographic features, the second part was related to the educational attitude, and the third part was related to Olson's standard questionnaire. The data were analyzed in SPSS 19 by statistical tests, t-test, and variance analysis. Results: The average age of students was 21.65±1.63 and 36 participants were female and 26 participants were male. 34 participants were educating in semester 4 and 28 participants were educating semester 8. The average score of educational attitude was 87.01±9.20 and the average score of ethical climate was 15.58±92.85, and the significant relationships were observed between the ethical climate and educational attitude (p=0.03). Conclusion: The results of this study showed that students have a positive view of their field of study and existence ethical climate and managers, and officials should try to maintain this situation, and the relationship between the ethical climate and educational attitude was significant. Keywords: Educational attitude, Ethical climate, The university students, Operating rooms.